2019
DOI: 10.1002/cam4.2157
|View full text |Cite
|
Sign up to set email alerts
|

Association between frailty syndrome and survival in patients with pancreatic adenocarcinoma

Abstract: Background Frailty is a syndrome characterized by weakness, slow gait, weight loss, exhaustion, and low activity. We sought to determine whether frailty was associated with age or stage in newly diagnosed patients with pancreatic ductal adenocarcinoma (PDAC), and determine its association with survival. Methods Consecutive patients with newly diagnosed PDAC of all stages underwent baseline assessment. Frailty (per Fried criteria) was defined as having three or more abnormalities in: grip strength, gait speed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
2
25
1
Order By: Relevance
“…This holds particularly true with pancreatic and biliary malignancies that frequently present with cachexia, frailty, and functional decline, regardless of age. 64 The frailty phenotype is also independent of cancer stage at diagnosis and associated with a significantly worse survival. Therefore, it becomes imperative to assess all patients for frailty and, further, attempt to improve physiologic status before major oncologic resection.…”
Section: Discussionmentioning
confidence: 99%
“…This holds particularly true with pancreatic and biliary malignancies that frequently present with cachexia, frailty, and functional decline, regardless of age. 64 The frailty phenotype is also independent of cancer stage at diagnosis and associated with a significantly worse survival. Therefore, it becomes imperative to assess all patients for frailty and, further, attempt to improve physiologic status before major oncologic resection.…”
Section: Discussionmentioning
confidence: 99%
“…19 Frailty, which is a syndrome characterized by weakness, slow gait, weight loss, exhaustion, and low activity, is prevalent among patients undergoing treatment for pancreatic cancer and has been associated with postoperative complications and reduced survival. 19,20 Sarcopenia has also been associated with reduced survival, but improved disease-free survival may be observed in patients in whom skeletal muscle is preserved during treatment. 5,21 Furthermore, patients receiving preoperative treatment may be at risk for further decline in physical function.…”
Section: Introductionmentioning
confidence: 99%
“…This phenotype was shown to be preceding functional decline in population-based studies, 3e5 and recent developments of research suggested an association with adverse outcomes in clinical settings, as it was also linked, among others, with surgical complications 6 or with mortality in patients with cancer. 7 In the process of operationalizing each frailty phenotype's dimension by measurable criteria, Fried et al separated participants according to the sex-specific 80th percentile (p80) for continuous variables. The time to perform a walking test at usual pace was dichotomized, and slowness was defined by a time > p80.…”
mentioning
confidence: 99%